Uterine Rupture at 21 Weeks in Twin Pregnancy with TTTS and Previous C-Section - Gieta Bhikha-kori; Marieke Sueters; Johanna M. Middeldorp (Case Reports in Obstetrics and Gynecology)
Uterine rupture is a health problem in every country. The diagnosis is not always obvious and fetal and maternal morbidity and mortality can be high.